2004
DOI: 10.1016/j.neuroimage.2004.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse optical imaging of brain activation: approaches to optimizing image sensitivity, resolution, and accuracy

Abstract: Near-infrared spectroscopy (NIRS) and diffuse optical imaging (DOI) are finding widespread application in the study of human brain activation, motivating further application-specific development of the technology. NIRS and DOI offer the potential to quantify changes in deoxyhemoglobin (HbR) and total hemoglobin (HbT) concentration, thus enabling distinction of oxygen consumption and blood flow changes during brain activation. While the techniques implemented presently provide important results for cognition an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
574
1
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 654 publications
(581 citation statements)
references
References 133 publications
(155 reference statements)
4
574
1
2
Order By: Relevance
“…During forepaw stimulation the electrodes near the primary somatosensory cortex (SI) resolve the characteristic SEP components, which correspond to SI activation. DOI has been used to measure hemodynamic evoked responses in several cortical areas in both humans and animals (Boas et al, 2004;Durduran et al, 2004;Gibson et al, 2005;Hillman et al, 2007;Hoshi, 2003;Obrig and Villringer, 1997;Villringer and Chance, 1997). Previously, we have shown that in rats we are able to detect evoked hemodynamic responses both spatially and temporally equivalent to fMRI (Culver et al, 2005;Culver et al, 2003;Siegel et al, 2003).…”
Section: Introductionmentioning
confidence: 93%
“…During forepaw stimulation the electrodes near the primary somatosensory cortex (SI) resolve the characteristic SEP components, which correspond to SI activation. DOI has been used to measure hemodynamic evoked responses in several cortical areas in both humans and animals (Boas et al, 2004;Durduran et al, 2004;Gibson et al, 2005;Hillman et al, 2007;Hoshi, 2003;Obrig and Villringer, 1997;Villringer and Chance, 1997). Previously, we have shown that in rats we are able to detect evoked hemodynamic responses both spatially and temporally equivalent to fMRI (Culver et al, 2005;Culver et al, 2003;Siegel et al, 2003).…”
Section: Introductionmentioning
confidence: 93%
“…We benefited both advantages in the development of our fNIRS system. For review and discussion over existing methods and systems, see (Strangman et al, 2002a, Hoshi, 2003, Obrig and Villringer, 2003, Boas et al, 2004, Wolf et al, 2007.…”
Section: Instrumentationmentioning
confidence: 99%
“…It is well known that the wavelength pairs 830 and 750 nm, or 830 and 690 nm are best suited because the wavelengths in these pairs lie above and below the isobestic point of 805 nm, where oxyhemoglobin and deoxy-hemoglobin have the same intrinsic absorption coefficient. 20 The above wavelength pairs minimize random wavelength dependent measurement errors as well as systematic errors arising from inaccuracies in model parameters. 20 With this in mind, laser diodes of wavelengths 685 ͑close to 690 nm͒ and 830 nm are used as diodes of these wavelengths are readily available.…”
Section: A Transmittermentioning
confidence: 99%
“…20 The above wavelength pairs minimize random wavelength dependent measurement errors as well as systematic errors arising from inaccuracies in model parameters. 20 With this in mind, laser diodes of wavelengths 685 ͑close to 690 nm͒ and 830 nm are used as diodes of these wavelengths are readily available. As detailed in Sec.…”
Section: A Transmittermentioning
confidence: 99%